A survey of relationship between social support with quality of life as well as stress among pregnant women referred to Shahryar hospital affiliated to social security organization in 1391 - Shishehgar, Sara; Dolatian, Mahrokh; bakhtiari, Maryam; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Pregnancy is the most stressful event in every woman’s life. Stress during pregnancy, delivery and breastfeeding may contribute to poor pregnancy outcomes and post partum psychological disorders. Social support is the most powerful factor for easy and successful confronting with stressful situations(for instance pregnancy).Increasing of survival and life-quality promotion are the result of social support.This study was conducted to determine the relation between social support,quality of life and stress rate during pregnancy. Method: This descriptive-correlational study was conducted in Shahryar hospital among 210 pregnant women who were selected by convenient sampling method.A demographic and obstetrical questionnaire, Vaux social support appraisal scale ,WHO quality of life and pregnancy stress questionnaire were used for data collection. Validity of questionnaires was assessed by face, content and construct methods, and reliability was assured by test re- test and conducting Alpha Cronbach’s reliability test. Statistical tests of Spearman and pearson correlation,T-test,One-way ANOVA and Tuckey were used for data analysis by SPSS package(version 19). Results: The mean score of social support, life-quality and stress were 17.66 and 88 respectively. A significant correlation was found between social support and life-quality. While this relation was not seen between social support and pregnancy stress. Whereas, there was a significant correlation between life-quality and pregnancy stress. Discussion: With respect to the results, samples enjoy of reasonable social support and life-quality while they suffered from moderate stress. Since social support lead to promotion of life-quality and this event could decrease the pregnant’sstress,it is necessary to design some solutions to increase the pregnant women’s social support. Key words: Social support, Quality of Life, Stress,Pregnancy.